A Rare Case of Craniofacial Morphology with Absent Face and Neck Structures, with Its Review - Lokadolalu Chandracharya Prasanna (Journal of Clinical and Diagnostic Research, 2013)
The development of the head and the face requires an intimate interaction between two mesenchymal populations, a paraxial mesoderm and neural crest cells for the morphogenesis of the musculoskeletal components of the calvaria, the face and the branchial regions. The disruptions in these interactions can cause foetal fatalities or congenital craniofacial anomalies. We are describing a rarest case with a craniofacial malformation, who was born with complete absence of the facial skeleton and the neck structures, a set of well developed ears in their normal locations and eyelids at the junction between the head and the thorax.